Albinism – symptomatology, aetiology, and therapy - Chałupczyńska, Beata; Ciara, Elżbieta; Chrzanowska, Krystyna H.; Madej-Pilarczyk, Agnieszka (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Albinism is a rare, genetically determined disorder of melanogenesis resulting in a reduction or complete absence of melanin in tissues of ectodermal origin, especially skin, hair, and irises of the eyes. It may occur in isolated form as oculocutaneous albinism inherited in an autosomal recessive manner or ocular albinism inherited in an X-linked recessive manner. Syndromic forms of albinism may additionally include involvement of other systems with various combination of symptoms and signs. The paper presents the classification, clinical characteristics, pathogenesis, and genetic basis of various forms of isolated and syndromic albinism. The diagnostic approach and available therapeutic interventions have been discussed.